Glenosphere design affects range of movement and risk of friction-type scapular impingement in reverse shoulder arthroplasty. (September 2018) - Werner, B. S.; Chaoui, J.; Walch, G.
Abstract : Aims: Scapular notching is a frequently observed radiographic phenomenon in reverse shoulder arthroplasty (RSA), signifying impingement of components. The purposes of this study were to evaluate the effect of glenoid component size and glenosphere type on impingement-free range of movement (ROM) for extension and internal and external rotation in a virtual RSA model, and to determine the optimal configuration to reduce the incidence of friction-type scapular notching. Materials and Methods: Preoperative CT scans obtained in 21 patients (three male, 18 female) with primary osteoarthritis were analyzed using modelling software. Two concurrent factors were tested for impingement-free ROM and translation of the centre of rotation: glenosphere diameter (36 mm vs 39 mm) and type (centred, 2 mm inferior eccentric offset, 10° inferior tilt). Results: Glenosphere size was most predictive of increased extension and external rotation, whereas lateralization of the centre of rotation was the most predictive factor for internal rotation. A larger diameter of glenosphere combined with a 10° tilted configuration demonstrated superior values for extension and external rotation, whereas the eccentric component improved internal rotation by a mean 8.9° (standard deviation 2.7°) compared with a standard concentric glenosphere. Conclusion: Glenosphere configuration can be modified to increase range of movement in RSA. Friction-type scapular notching was most effectively reduced by use of a large-diameter glenosphere with 10° inferior tilt. Cite this article: Bone Joint J 2018;100-B:1182–6.